The Use of Elements of Film Expression and their Role in Narrative Transitions: محمد أكرم عبد الجليل (Al-Academy, 2019)
Many studies and researches related to the audio and visual medium have shed light on the creative process that has taken place through them as well as the aesthetic and artistic creation and have dealt with many fields of knowledge and creativity in this field of art, which managed to study and follow its intellectual and technical tools for creating achievements through this medium, in its forefront come the elements of the cinematic language, which is characterized by possessing multiple features of aesthetic and semantic employment to reach the recipient as it is a tool of the artistic expression that gives the material it deals with aesthetic and intellectual dimensions from various aspects. "The artistic expression cannot be achieved except through a substance in order to turn into that stimulant or sensory stimulant, and in this way it can be the pronunciation or the sound or the movement or the stones ... etc. But the raw material does not acquire an artistic nature turning into an aesthetic material until the artist's hand extends to it creating from it an aesthetic sense (As-Sayyid, 2008: p 46). The problem of the research is the role of elements of cinematic expression in the narrative transitions within the structure of cinema and television work, and the differences between them remain according to the nature of the artistic treatment. The research consists of three sections the first is entitled the transitions as narrative ways, while the second is entitled the film narrative construction and the narrative perspective. The third section is entitled the Narration and the Expression. The research sample was the film (The English Patient). The film scenario was written and directed by Anthony Minghella 1996. The researcher reached a number of results and the most prominent of which was the manifestation of the relationship between the narrative structure of the film and the novel perspective through an implicit relationship as a set of juxtapositions and mutual directions between the art of the film and the art of the novel.